2018
DOI: 10.1021/acs.nanolett.8b04534
|View full text |Cite
|
Sign up to set email alerts
|

Microfocus Laser–Angle-Resolved Photoemission on Encapsulated Mono-, Bi-, and Few-Layer 1T′-WTe2

Abstract: Two-dimensional crystals of semimetallic van der Waals materials hold much potential for the realization of novel phases, as exemplified by the recent discoveries of a polar metal in few layer 1T'-WTe 2 and of a quantum spin Hall state in monolayers of the same material. Understanding these phases is particularly challenging because little is known from experiment about the momentum space electronic structure of ultrathin crystals. Here, we report direct electronic structure measurements of exfoliated mono-bi-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 34 publications
(123 reference statements)
8
85
0
Order By: Relevance
“…Most importantly, the model has an indirect energy gap of ∆E = 56 meV, compatible with experiments. 37,40,50 Moreover, close to the Fermi level, the dispersion of our model matches experimental results 40,50 by construction. An analysis of the parities ξ of the states at the four time-reversal invariant momenta Γ, X, Y , and M shows that the lowest conduction band and the lowest valence band in our model are inverted at Γ [see Fig.…”
Section: B Spin-orbit Coupling From Symmetriessupporting
confidence: 82%
See 2 more Smart Citations
“…Most importantly, the model has an indirect energy gap of ∆E = 56 meV, compatible with experiments. 37,40,50 Moreover, close to the Fermi level, the dispersion of our model matches experimental results 40,50 by construction. An analysis of the parities ξ of the states at the four time-reversal invariant momenta Γ, X, Y , and M shows that the lowest conduction band and the lowest valence band in our model are inverted at Γ [see Fig.…”
Section: B Spin-orbit Coupling From Symmetriessupporting
confidence: 82%
“…The edges of typical samples used in experiments on 2D monolayer materials are highly irregular, i.e., they have cracks, steps or bumps. 42,50 Hence, the samples are no longer translationally invariant along their boundary, enabling backscattering of edge states when time-reversal symmetry is broken. We model a rough edge by the boundary following a random walk with a step appearing at every site with probability p (see Supplemental Material 47 for details).…”
Section: Ribbons With Disordered Edges Under Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…While the presence of a large gap of >60 meV in monolayer WTe2 is demonstrated by transport [3] and ARPES [12] measurements, the semiconductor versus semimetallic nature of the bilayer remains unclear. ARPES experiments on bi-layer WTe2 [12] indicate a vanishing, if not negative, gap (Fig. 4d and 4e).…”
mentioning
confidence: 99%
“…Bi-layers exhibit a narrow gap (<10 meV) semiconducting behavior in transport measurements [3]. Angle resolved photoemission spectroscopy (ARPES), however, revealed that bi-layers could also be weakly semimetallic with a small negative gap [12]. A combination of inverted bands, strong spin-orbit coupling and low crystal symmetry makes few-layer WTe2 an ideal system for studying topological effects such as the nonlinear anomalous Hall effect [13] [14] [15] and various unusual photogalvanic effects [16] [17] [18].…”
mentioning
confidence: 99%